2005
DOI: 10.1292/jvms.67.223
|View full text |Cite
|
Sign up to set email alerts
|

Antibabesial Activity of Protoberberine Alkaloids and 20-Hydroxyecdysone from Arcangelisia flava against Babesia gibsoni in Culture

Abstract: ABSTRACT. Bioassay-guided fractionation of the boiled extract from the stems of Arcangelisia flava led to the isolation of palmatine (1), berberine (2), jatrorrhizine (3), dihydroberberine (4) and 20-hydroxyecdysone (5). The chemical structures of these compounds were elucidated on the basis of their chemical and spectral evidence. The isolated compounds were evaluated for their growth inhibiting effects on Babesia gibsoni in culture for a week. Compounds (1-4) showed significant inhibitions at concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…), a liana in the Menispermaceae family, grows throughout South East Asia. It has been used traditionally to treat malaria, dysentery, and fever (Subeki et al 2005;Larisu 2011). The plant has 96 WULANSARI ET AL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), a liana in the Menispermaceae family, grows throughout South East Asia. It has been used traditionally to treat malaria, dysentery, and fever (Subeki et al 2005;Larisu 2011). The plant has 96 WULANSARI ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloid dehydrocorydalamine, thalifendine, and palmatine have been isolated as minor compounds (Verpoorte et al 1982). Some of the alkaloids, including palmatine, berberine, jatorrhizine, dihydroberberine, and 20-hydroxyecdysone, proved to be active agents against Babesia gibsoni, a parasite which causes disease in domestic animals (Subeki et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Further derivatization of dihydroberberine by the introduction of hydroxy and cyano groups onto the reduced ring leads to active antimalarials (Vennerstrom & Klayman, 1988), avian myeblastosis virus inhibitors (AMV–RT) (Kusumoto et al , 1991), antitumour agents (Kim et al , 1997), antifungals (Dostál et al , 1999), mitogen-activated protein kinase inhibitors (MAPKK) (Jang et al , 2002), promoters of glucose metabolism and insulin secretion (Xu et al , 2011), and CD36 antagonists (Li et al , 2010). Dihydroberberine has found use as an intermediate in the synthesis of substituted berberine analogues which were found to act as anticancer agents (Zhang et al , 2012), pancreatic lipase inhibitory agents (Mohammad et al , 2013), antifungal agents (Li et al , 2013), Toxoplasma gondii inhibitors (Krivogorsky et al , 2012), and mitochondria-targeted antioxidants (Lyamzaev et al , 2011), and which have shown activity as antibabesial (Subeki et al , 2005) and antileishmania agents (Marquis et al , 2003) and as HIV-1 RT inhibitors (Vennerstrom et al , 1990). …”
Section: Introductionmentioning
confidence: 99%
“…Archetypal ecdysteroid, 20-hydroxyecdysone, was able to inhibit in vitro multiplication of another apicomplexan parasite Babesia gibsoni [81], however, when examined by our team against T. gondii, surprisingly promoted in vitro proliferation of the protozoan [82]. The problem requires a further study because some food plants are a rich source of different phytoecdysteroids at high concentrations and, besides, many of them are essential components of widely used anabolic preparations.…”
Section: Compounds Of Natural Originmentioning
confidence: 86%